EKSPLORASI KANDUNGAN FENOLIK TOTAL BUAH OKRA (Abelmoschus esculentus L.) SEBAGAI KANDIDAT PRODUK HERBAL - Mega Efrilia; Yulius Evan Christian Evan; Pra Panca Bayu Chandra; Ema Hermawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Okra fruit (Abelmoschus esculentus L.) is a plant that contains phenolic and flavonoid compounds that have the potential as natural antioxidants and can be utilized in pharmaceutical formulations and health products. This study aims to determine the total phenolic content in 70% ethanol extract of okra fruit and evaluate its physical characteristics. The method used in this study consists of several stages. Extraction was done using the maceration method, with 1,005.88 grams of simplistic powder soaked in 10 liters of 70% ethanol for 5 days, stirring every 24 hours. After maceration, the filtrate from the extraction is filtered using Whatman No.1 filter paper, then evaporated using a rotary vacuum evaporator at 40°C until a thick extract is obtained. The extract obtained was tested for physical characteristics through organoleptic testing, including color, odor, and taste. Furthermore, total phenolic content was determined using the Folin-Ciocalteu method, with gallic acid (GAE) as a standard. Absorbance measurements were taken using a UV-Vis spectrophotometer at a wavelength of 765 nm. The results showed that the thick extract yielded 9.47%, with a DER-native value of 10.56. Organoleptic tests showed that the extract had a blackish-brown color, a distinctive odor of okra fruit, and a bitter taste with a slight tartness, indicating the presence of phenolic compounds and tannins. Determination of total phenolic content showed that okra fruit extract had a phenolic content of 921.21 mg GAE/g extract, which showed potential as a natural antioxidant. The 70% ethanol extract of okra fruit has high phenolic content, so it has the potential to be used as a natural antioxidant in pharmaceutical formulations and natural ingredient-based health products.